Pelatihan Pendidikan Seks Anak Usia Dini Pada Kader ‘Aisyiyah Ranting Pandeyan Kecamatan Umbulharjo Kota Yogyakarta - Wijhati, Ellyda Rizki; Suharni, Suharni (Aksiologiya: Jurnal Pengabdian Kepada Masyarakat, 2018)
Age 0-6 years is a period of "golden age" very important and determine the quality of life of children later. Nowadays there are many sexual violence with child victims, caused by weakness of parental supervision and not optimal of sex education in children. Children are particularly vulnerable to being sexually assaulted as being powerless to take action against the perpetrators. Sex education is an effort that can be done to prevent the sexual violence, but many parent assume that sex education is a taboo, less important, children will get that knowledge in school so many parents who do not provide sex education in children. As a result, the child does not have sufficient knowledge about sexual health and cannot protect himself if he experiences violence or sexual harassment. Training activities are expected to increase the knowledge and awareness of cadres of the importance of providing sex education in children. Implementation of the training is done for 2 meetings with a duration of 5 hours. The first meeting discussed the urgency of providing sex education in children and Focus Group Discussions (FGD). The second meeting discussed ways of providing sex education and materials to be conveyed to children about their reproductive health, question and answer discussion, and production healthcare cadres. The results of training there is an increase in the level of knowledge and changes in perception of sex education in children and the establishment of reproductive health cadres.